METODE COOKING SEBAGAI UPAYA PENGENTASAN GIZI KURANG DAN GIZI LEBIH BALITA DI DESA CATUR, KINTAMANI, BANGLI, BALI - Ni KETUT WIRADNYANI; Ni Wayan Nursini; Ni Putu Eny Sulistyadewi; Purwaningtyas Purwaningtyas; I Gusti Ayu Wita Kusumawati; Ida Bagus Agung Yogeswara; I Gede Mustika; Dylla Hanggaeni Dyah Puspaningrum (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2021)
The purpose of community service by the Dhyana Pura University Nutrition Program Study applying the cooking method is to provide knowledge, skills to Posyandu, foster mothers who have under-fives and more. The solution that has been given by the method of cooking by moist heat and dry heat in processing various food ingredients from plant and animal origin makes a menu of less nutrition and more nutrition through lectures, demonstrations and question and answer methods. The results of the post-test stated that 88% of the posyandu community and foster mothers with less and more nutrition in toddlers aged 2 -5 years knew how to use the cooking method in making teplon pizza, purple sweet potato bread and pudding, soup pumkin, egg dishes, soto radish, capcay, breaded catfish satay, pumpkin bread, green bean juice, in the presentation of the lectures as well as the skills and target of achieving solutions that partners expect to increase from the pre-test results of 11,5%. From this activity the knowledge and ability of foster mothers and posyandu groups increased regarding the cooking method used in processing plant and animal food ingredients for alleviating the problem of undernutrition and increased by 22%. Keywords: Over nutrition, less nutrition, Moist heat, Dry heat, Catur Village